Assessing the needs of pedestrian facilities at Tiruchirappalli, India - Rajendra Babu; Subbaiyan; Srinivas Tadepalli (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Walking is an inherent part of journeys of majority of people living in Indian cities. Walking has many advantages ranging from individual’s health to environmental issues. Although significant number of trips is made on foot the current practices of municipal administrations underestimate the importance of walking. The urban streets and roads have been designed taking into consideration the requirements of vehicular growth and neglecting the requirements of pedestrians. In most of Indian cities the pedestrian facilities are either inadequate or non-existent. This study investigated the present state of pedestrian facilities and assessed the needs of pedestrians on the main streets of various land use zones in Tiruchirappalli City, Tamil Nadu state, India. Field studies were carried out using survey tool kits that include Global Walkability Index (GWI) developed by Holly Virginia Krambeck, Pedestrian infrastructure observation sheet and Pedestrian preference questionnaire. The walkability indices of streets in mixed residential zones were maximum and walkability indices of streets in residential zones were minimum. In the surveyed streets the sidewalks are either inadequate or not present. The existing pedestrian paths are mainly encroached by street vendors and parking of vehicles. The pedestrian facilities along the pedestrian paths are almost non-existent. The most important concerns of pedestrians include issues such as personal security, inadequate street lighting, encroachment on pedestrian platforms, lack of well connected and well maintained pavements. Based on the observations of existing pedestrian facilities and assessment of pedestrian needs this paper proposes pedestrian-focused solutions to improve walkability.